Delay in administration of estates: causes and implications - Mohd Salim, Wan Noraini; DrsNasrul, Muhammad Amrullah (Faculty of Law, Accountancy and International Relations, UniSZA, 2015)
The time duration for actual distribution of the deceased’s estate depends on the smooth process in estate administration. Apart from the personal representative, the beneficiaries also play an important role in the administration as the recipients of the deceased’s estate as well as participants in the administrative process itself. Thus, it is necessary that as participants, all the beneficiaries must cooperate and work hand in hand to ensure that the process goes without any difficulties, which could adversely affects the overall process. This paper addresses the problem of delay in the administration of estate and analyses its causes and implications in the distribution of the estate. The lack of knowledge on the law of succession and the attitude of the beneficiaries are the key factors, which lead to such problem. This paper is based primarily on the analysis of written sources namely conference papers, text books, statutes, case laws, journals and other library based documents. This paper shows that there is a need for a cohesive approach to educate the beneficiaries of the law and to change their attitude in understanding their actual roles in the deceased’s estate administration.